Generative Design Strategies for Lightweight Internal Structure in Tandem Wing Small UAVs - BUICAN, George Răzvan; AGAPIE, Constantin-Mihăiță (Publishing House of “Henri Coanda” Air Force Academy, 2024)
This research employs generative design methodologies to optimize the internal structure of a small unmanned aerial vehicle (UAV) configured with tandem wings, with the explicit goal of achieving a lightweight architecture. The need for UAV internal structures to prioritize weight reduction while upholding structural integrity facilitates the application of generative design techniques. Through a meticulous analysis of generative design principles and their application in UAV structural engineering, this study highlights the potential advantages and challenges inherent in integrating generative design strategies into the development of tandem wing UAVs. The insights presented aim to underscore the opportunities involved in harnessing generative design methodologies to achieve lightweight yet robust internal structures for tandem wing small UAVs.
This paper was presented at the International Conference of Scientific Research and Education in the Air Force – AFASES 2024, Brașov, Romania. It was published in open access by the Henri Coandă Air Force Academy Publishing House. DOI: 10.19062/2247-3173.2024.25.16.
Keywords: Aerospace; Fixed-Wing UAV; Generative Design; Additive Manufacturing